2014
DOI: 10.12816/0023980
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Systemic Delivery of Aminoguanidine Versus Doxycycline on the Resorptive Phase of Alveolar Bone Following Modified Widman Flap in Diabetic Rats : A Histopathological and Scanning Electron Microscope ( SEM ) Study

Abstract: Abstract:Objectives: Aminoguanidine (guanylhydrazinehydrochloride) is a drug that prevents many of the classical systemic complications of diabetes including diabetic osteopenia through its inhibitory activity on the accumulation of advanced glycation end -products (AGEs). The aim of the present study was to evaluate the effectiveness of aminoguanidine versus doxycycline in reducing alveolar bone resorption following mucoperiosteal flap in diabetic rats, using the conventional histopathology and scanning elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…Importantly, blockade of RAGE in DM mice orally treated with P. gingivalis reduced TNF-α and IL-6 production and periodontal bone loss [ 176 ]. Furthermore, treatment of LIP-DM rats with aminoguanidine, which prevents AGE accumulation, reduced inflammatory cell infiltration, increased osteoblast number, and reduced osteoclast number [ 177 ], confirming the importance of AGE-induced inflammation in coupling DM to periodontal destruction.…”
Section: Mechanisms Linking Periodontitis and Dmmentioning
confidence: 99%
“…Importantly, blockade of RAGE in DM mice orally treated with P. gingivalis reduced TNF-α and IL-6 production and periodontal bone loss [ 176 ]. Furthermore, treatment of LIP-DM rats with aminoguanidine, which prevents AGE accumulation, reduced inflammatory cell infiltration, increased osteoblast number, and reduced osteoclast number [ 177 ], confirming the importance of AGE-induced inflammation in coupling DM to periodontal destruction.…”
Section: Mechanisms Linking Periodontitis and Dmmentioning
confidence: 99%
“…Moreover, Özdemir et al 7 found that LDD administration did not affect alveolar bone levels in the diabetic rat with ligature-induced periodontitis. On the contrary, Tella et al 105 analyzed the effects of LDD on periodontal defects by experimentally inducing on the lower anterior teeth using an orthodontic elastic ligature in diabetic rats. They found that there was a significant increase of the number of osteoblasts and decreased number of osteoclasts and inflammatory cell infiltration in the doxycycline treated group when compared to control group.…”
Section: Effect Of Low-dose Doxycycline Therapy On Alveolar Bone Lossmentioning
confidence: 99%
“…LDD was also effective in decreasing bone resorping activity in the diabetic rats. 105 It asserted that the results of studies can be effected some factor, such as the number of rats in the study, excessive trauma caused during defect preparation, nonoptimum defect size, and variable glucose levels in the rats. …”
Section: Effect Of Low-dose Doxycycline Therapy On Alveolar Bone Lossmentioning
confidence: 99%
“…The specimens were then dehydrated in the graded series of aqueous ethanol solution 50%, 70%, 90%, and 100% for one hour for each specimen. Then they were airdried, mounted on aluminum SEM stubs with silver paint and sputter coated with gold using an ion coater (sputter coater) (29). The specimens were examined by SEM using a 20-kV accelerating voltage; to observe the alveolar bone surface integrity buccally using magnifications X500 & X3500.…”
Section: Scanning Electron Microscopic (Sem) Examination: (29 30)mentioning
confidence: 99%